Analisis Budaya Kerja, Kompetensi dan Prestasi Kerja Terhadap Kinerja Karyawan di PT Perkebunan Nusantara III - Irawadi; Yanti, Eli Delvi; Pratama , Siswa (Universitas Negeri Medan, 2025)
This research aims to find out and analyze work culture, competencies and work achievements onemployee performance. The location of this research was carried out at PT Perkebunan Nusantara III. This typeof research is a descriptive analysis method with a quantitative approach. The analysis used is multiple linearregression analysis. The number of samples in this study is a multiple linear regression analysis method with thehelp of SPSS software version 25. Partially, the results of this study show that work culture (X1) has no influenceon employee performance. Competence (X2) has a significant positive influence on employee performance. Workperformance (X3) has a significant positive influence on employee performance. Meanwhile, simultaneously thevariables of work culture (X1), competence (X2) and work performance (X3) together have a significant positiveeffect on employee performance.